2021
DOI: 10.3390/ma14040928
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Performance of Additively Manufactured AISI H13 Steel in Different Surface Conditions

Abstract: Additive manufacturing of metallic tribological components offers unprecedented degrees of freedom, but the surface roughness of most as-printed surfaces impedes the direct applicability of such structures, and postprocessing is necessary. Here, the tribological performance of AISI H13 steel samples was studied. These were additively manufactured through laser powder bed fusion (L-PBF), also referred to as selective laser melting (SLM). Samples were tested in four different surface conditions: as-printed, poli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…These requirements are commonly set by specific surface-texture parameter targets, from the most used Ra (and areal Sa) to parameters related to material ratio curve. It was shown that even manually-removed material using coated abrasives (220-1200 mesh), combined with short-time polishing using a diamond slurry, can reduce as-built surface texture of PBF-LB/X40CrMoV5-1 tool steel to mirror-like finish at Sa = 0.15 μm [248]. The as-built layer (30 μm thick) here could not be removed by polishing alone, but the combined abrasive post-processing lowered the friction coefficient by about one order of magnitude (i.e., from 0.1 for as-built to 0.01 of finished sample).…”
Section: Impact On Tribological Performancementioning
confidence: 99%
“…These requirements are commonly set by specific surface-texture parameter targets, from the most used Ra (and areal Sa) to parameters related to material ratio curve. It was shown that even manually-removed material using coated abrasives (220-1200 mesh), combined with short-time polishing using a diamond slurry, can reduce as-built surface texture of PBF-LB/X40CrMoV5-1 tool steel to mirror-like finish at Sa = 0.15 μm [248]. The as-built layer (30 μm thick) here could not be removed by polishing alone, but the combined abrasive post-processing lowered the friction coefficient by about one order of magnitude (i.e., from 0.1 for as-built to 0.01 of finished sample).…”
Section: Impact On Tribological Performancementioning
confidence: 99%
“…The test part (shown in Figure 2) was designed using CAD software (SolidWorks 2021, version number: 6.30.1030, Dassault Systèmes, Vélizy-Villacoublay, France) and manufactured using the SLM 125HL machine (SLM Solutions AG, Lubeck, Germany). There is also an additional factor that is very important in the case of hydraulic solutions, and at the same time, it is one of the biggest weaknesses of AM-the high surface roughness of the as-built parts [48][49][50][51][52][53][54]. In the case of H13 tool steel, Guenther et al [52] revealed that in the case of such steels, a direct correlation between surface roughness and friction coefficient, i.e., the rougher the surface was, the higher the friction force, does not take place.…”
Section: Manufacturing Process Descriptionmentioning
confidence: 99%
“…There is also an additional factor that is very important in the case of hydraulic solutions, and at the same time, it is one of the biggest weaknesses of AM—the high surface roughness of the as-built parts [ 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. In the case of H13 tool steel, Guenther et al [ 52 ] revealed that in the case of such steels, a direct correlation between surface roughness and friction coefficient, i.e., the rougher the surface was, the higher the friction force, does not take place.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Nowadays, it is well known that despite such good research results on the mechanical properties of the AM parts, anisotropy plays an important role in the performance properties, which is especially important in some industrial applications. [4,5] From the point of view of fatigue properties, it is very important to take into account some technologically based issues, such as porosity, [6,7] the increased surface roughness of the as-build parts, [8,9] residual stresses, [10,11] or the influence of build orientation during the process. [12,13] The phenomenon related to the occurrence of lower fatigue strength of AM parts could be compensated by adjusting the geometry of the parts to the so-called ''Design for Additive Manufacturing.''…”
Section: Introductionmentioning
confidence: 99%